Comparative QTL map for white mold resistance in Common Bean, and characterization of partial resistance in dry bean lines VA19 and I9365-31 - Soule, M; Porter, L.; Medina, JI; Santana, GP; Blair, Matthew W.; Miklas, PN (Wiley, 2011)
White mold caused by the necrotrophic fungus Sclerotinia sclerotiorum (Lib.) de Bary limits common bean (Phaseolus vulgaris L.) production in temperate climates. Disease resistance has been identified, but breeding is hampered by a paucity of resistance sources and complex inheritance, as numerous quantitative trait loci (QTL) conditioning partial resistance have been found. Our objectives were to characterize the partial white mold resistance found in breeding lines I9365-31 and VA19 and to construct a comparative linkage map for all the white mold resistance QTL identified to date. Recombinant inbred line (RIL) populations ‘Benton’/VA19 (BV) and ‘Raven’/I9365-31 (R31) consisting of 79 F6 and 105 F5 RILs, respectively, were evaluated for white mold (WM) reaction in multiple greenhouse and field tests. Two QTL were found in BV, WM2.2 expressed in the greenhouse (R2 = 33%) and the field (13%) and WM8.3 expressed in field (11%) only, and seven were found in R31 (WM2.2, WM4.2, WM5.3, WM5.4, WM6.1, WM7.3, WM8.4), three expressed in greenhouse tests and four in the field, ranging in phenotypic variance from 5 to 52%. These QTL were compared with 26 previously identified QTL, resulting in a comparative linkage map of 35 QTL, which coalesced into 21 distinct regions across nine linkage groups. Four QTL found in R31 were novel. Sequence characterized amplified region markers associated with WM2.2, WM8.3, and WM7.3 QTL were generated. The comparative linkage map provides a framework for integrating and interpreting future QTL studies concerning white mold resistance in common bean.